Selected personality traits as predictors of coping flexibility in a group of officers of the State Fire Service - Ewa Stępka-Tykwińska; Małgorzata Anna Basińska; Michalina Sołtys; Anna Piórowska (Nofer Institute of Occupational Medicine, 2019)
Background The flexibility in coping with stress is a new construct in Europe, which allows for a more insightful understanding of individual coping mechanisms, perceived as a process of continuous search for more effective solutions. An individual who is capable of coping with stress in a flexible way, notices the lack of effectiveness of some methods of coping, seeks new solutions, has a wide repertoire of coping strategies, as well as shows reflexivity to see the lack of effectiveness in coping. The profession of a firefighter is characterized by a high level of stress, so people performing this profession should be aware of the remedial actions undertaken and their actual effectiveness. Material and Methods Altogether, 163 officers of the State Fire Service were examined. The following questionnaires were used in the study: the Polish adaptation of the Impulsiveness-Venturesomeness-Empathy (IVE) Questionnaire , the Coping Flexibility Questionnaire (Polish name: Kwestionariusz elastyczności w radzeniu sobie ze stresem - KERS-14), and a personal survey. Results Firefighters with more risky attitudes were found to display greater flexibility in coping, in terms of having a wider repertoire and variability in the applied strategies. In the case of officers with the shortest service period ( 14 years), the level of variation in coping strategies correlated positively with the level of empathy. Conclusions Risk taking propensity is an important predictor of flexibility in coping. The service period is a moderator (at the level of statistical tendency) of the relationship between empathy and flexibility in coping, especially in the field of variability in the use of coping strategies. Med Pr. 2019;70(5):555-65